Analisis Usability Sistem Aplikasi Kredit Digital Dengan Pendekatan Use Questionnaire dan IPA - Vellia Mulyani; Syarif Hidayatulloh (Jurnal Sistem Informasi, 2023)
Online loan applications are a form of cashless transaction with the number of users continuing to increase every year, especially in Indonesia. Various online credit and loan applications are born as if they are in demand by offering banking solutions and various promotions. One of the online loan and credit applications is the Kredivo application. This application has many features not only as a payment method, but also as a tool for making cash and credit payments to the markets that work with this application. So far, this application has never been analyzed, so researchers want to conduct research to obtain new findings about the usability of the Kredivo application system and as proof or testing of the correctness of existing knowledge, namely use questionnaire analysis and importance performance analysis. The results of his research show that the variables tested on the respondents are still not in accordance with the expectations of the respondents.